The effect of web-based education on self-care behaviors in cardiovascular patients: application of the pender's health promotion model - Homamodin Javadzade; Hakime Vahedparast; Azime Khodaminasab; Rahim Tahmasebi; Mahnoush Reisi; Jamile Kiani (BMC, 2024)
Abstract Background Coronary artery disease is the most common cardiovascular disease, the mortality rate of which is increasing significantly. The most important way to prevent a second attack in patients undergoing angioplasty is self-care, which can be influenced by several factors such as the patient's beliefs. Thus, the present study aimed to determine the effect of a web-based intervention based on the Pender's health promotion model in patients with cardiovascular disease. Methods The present clinical trial study was conducted with 99 patients undergoing angioplasty treatment referring to Bushehr Heart Specialist Center. Random sampling was done and the participants were divided into two groups (50 subjects in intervention group and 49 subjects in control group). The data collection tool was a three-part questionnaire (including demographic information, a researcher-made questionnaire based on the health promotion model constructs, and self-care behaviors), which was completed in three stages (before, two weeks, and three months after the intervention). In addition to routine hospital services, the intervention group received multimedia training based on the constructs of the Pender's health promotion model from the website. The control group received usual hospital services. Data were analyzed with chi-square, independent T-test and repeated measure ANOVA using SPSS-22 software. Results The results showed that 2 weeks and 3 months after the intervention, the mean scores of perceived benefits, perceived self-efficacy and perceived social support had a significant increase in the intervention group compared to the control group, but the mean score of perceived barriers had a significant decrease in the intervention group (p < 0.001). Regarding self-care behaviors, after the intervention, the mean scores of self-care behaviors, physical activity, healthy diet, medication adherence and stress management had a significant increase in the intervention group compared to the control group (p < 0.001), but no significant was observed between the two groups in terms of changes in the non-smoking (p = 0.38). Conclusion The results of the study showed that the web-based educational intervention based on the health promotion model is useful in improving the self-care behaviors of cardiac patients undergoing angioplasty. Nursing education and care have a great role in improving the self-care behaviors of cardiovascular patients. Trial registration Registration number: IRCT2017080635429N2. Registration date: 09/03/2017 ( https://en.irct.ir/trial/26775 ).